2019
DOI: 10.1017/wsc.2019.45
|View full text |Cite
|
Sign up to set email alerts
|

The influence of winter annual grass litter on herbicide availability

Abstract: Invasive winter annual grass infestations on rangeland accumulate large quantities of litter on the soil surface, as plants senesce yearly and decompose slowly. It has been speculated that winter annual grass litter can adsorb soil-active herbicides and reduce overall performance. Three experiments were conducted from 2017 to 2018 at the Colorado State University Weed Research Laboratory to evaluate interception and subsequent desorption of herbicides applied to litter from three invasive winter annual grass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 51 publications
2
14
0
3
Order By: Relevance
“…These results corroborate Clark et al (2019), who applied indaziflam on straw of Bromus tectorum and performed simulations of rainfall and found that a greater amount of the herbicide was intercepted when the applied on large amounts of straw, and the recovery of indaziflam intercepted in the straw was greater when the rainfall simulation occurred immediately after application of the product and with greater amounts of simulated rainfall.…”
Section: Control Of Urochloa Plantaginea By Indaziflam In Different Asupporting
confidence: 85%
“…These results corroborate Clark et al (2019), who applied indaziflam on straw of Bromus tectorum and performed simulations of rainfall and found that a greater amount of the herbicide was intercepted when the applied on large amounts of straw, and the recovery of indaziflam intercepted in the straw was greater when the rainfall simulation occurred immediately after application of the product and with greater amounts of simulated rainfall.…”
Section: Control Of Urochloa Plantaginea By Indaziflam In Different Asupporting
confidence: 85%
“…Herbicide efficacy can be improved with litter removal by fire (DiTomaso et al 2006). Herbicide interception by B. tectorum litter can be as high as 74% to 84% (Clark et al 2019a;Kessler et al 2015). Due to differences in water solubility, imazapic and rimsulfuron are almost completely released from litter with as little as 12 mm of rainfall, while <50% of indaziflam is released from litter with 24 mm of rainfall (Clark et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Herbicide interception by B. tectorum litter can be as high as 74% to 84% (Clark et al 2019a;Kessler et al 2015). Due to differences in water solubility, imazapic and rimsulfuron are almost completely released from litter with as little as 12 mm of rainfall, while <50% of indaziflam is released from litter with 24 mm of rainfall (Clark et al 2019a). This suggests that indaziflam binds strongly to litter (Carbonari et al 2016;Clark et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…É o caso de flumioxazin (solubilidade: 0,786 mg L -1 e log Kow: 2,55) (IUPAC, 2020) que apresentou um baixo controle de A. hybridus quando não foi realizada a dessecação complementar. Na ausência de chuvas significativas, herbicidas com baixa solubilidade e log Kow elevado tendem a ficar retidos na palha e não atingir o solo (CARBONARI et al, 2019;CLARK et al, 2019). Dessa forma a ação destes herbicidas pode ter sido comprometida, já que dependem do contato e absorção das moléculas pelas estruturas das plântulas em emergência (KRAUSZ; KAPUSTA; MATTHEWS, 1998;NIEKAMP;JOHNSON;SMEDA, 1999;CLEWIS;WILCUT;PORTERFIELD, 2006;MEYERS et al, 2010).…”
Section: Experimento IV -Programas De Manejo De Amaranthus Hybridus Aunclassified